Final answer:
The inverse of the function g(x) = 1/(x-1) is g^-1(x) = (1 + x)/x. The inverse function is a function if each x-value has a unique corresponding y-value.
Step-by-step explanation:
The inverse of the function g(x) = 1/(x-1) can be found by swapping the x and y variables and solving for y. Let's start with the original function:
g(x) = 1/(x-1)
Swap x and y:
x = 1/(y-1)
Now solve for y:
x(y-1) = 1
xy - x = 1
xy = 1 + x
y = (1 + x)/x
So, the inverse function is g-1(x) = (1 + x)/x. It is important to note that the inverse of a function is only a function if every value of x has a corresponding unique value of y, meaning that no two x-values can have the same y-value. In this case, the inverse function is indeed a function.